P654Left and right atria show different basal expression patterns of metabolic enzymes in a proteomic-based gene ontology representation study. (15th July 2014) - Dietl, A; Winkel, I; Deutzmann, R; Hupf, J; Riegger, G; Luchner, A; Birner, C
Abstract: Background: Left and right atria show compelling differences regarding organogenesis and specific clinical diseases, as exemplarily evidenced by a different arrhythmic susceptibility. This strongly indicates a diverging basal left and right atrial molecular set-up which has not been sufficiently characterised so far. Objective: To determine basal differences between left and right atrial protein expressions indicating interatrial differential molecular pathways. Methods: Left and right atrial whole proteome lysates of seven healthy rabbits were compared by two-dimensional gel electrophoresis. Significant differentially expressed proteins were identified by tandem mass spectrometry. Significantly differing proteins were classified according to their putative biological function. A gene ontology representation study was carried out using the PANTHER database tools of a binomial statistic test including a Bonferroni correction for multiple testing. To confine this analysis to the subset of proteins which is potentially identifiable upon two dimensional gel electrophoresis, a reference list was calculated in silico based on the UniProt Knowledgebase by the ExPASy-TagIdent tool including proteins with an isoelectric point 4.5 to 8 and molecular weights 25.5-144.5kDa. Results: Echocardiography showed normal left ventricular function and atrial morphology in the seven rabbits. Upon proteomic analysis, 39 proteins displayed significant expression differences between left and right atria. 18 of them were allocated in the mitochondria. The in silico calculated reference list comprised 7748 proteins. Three biological processes of metabolism were significantly overexpressed in the left atrium: generation of precursor metabolites and energy (p=1.1*10-4), oxidative phosphorylation (p=2.5*10-3) and respiratory electron transport chain (p=0.01). Conclusion: Left and right atria show significant differential expression of 39 proteins in a whole proteome study. Going beyond individual proteins to biological processes, a gene ontology representation study showed three components of energetic catabolism significantly overexpressed in the healthy left atrium. This result is consistent with the mitochondrial allocation of nearly half of the detected differential proteins. In conclusion, our data indicate an interatrial difference of the metabolic proteome. Further studies are necessary to identify underlying physiological causes and regulatory mechanisms.